Study of Stearic Acid Layer (SA) Microstructure on Surface Quartz Crystal Microbalance (QCM) Sensors - Nurramdaniyah Nurramdaniyah; Masdiana Padega; Djoko Herry Santjojo; Setyawan P. Sakti; Masruroh Masruroh (Natural B, Journal of Health and Environmental Sciences, 2017)
In the development of QCM-based biosensor sensors, the sensor surface is a very important part because it determine how the surface interacting with its environment especially during the immobilization of biomolecules process. In the utilization of QCM as biomolecule detecting biosensor, it is necessary to coat the polymer material on the surface of QCM. A stearic acid layer is used as an immobilization matrix layer because stearic acid has both polar and non polar properties so it can interact with biomolecules. The stearic acid layer is deposited on the polystyrene surface using a vacuum evaporation method. A study of the microstructure of the stearic acid coating was conducted to determine the possibility of the deposited stearic acid layer used as the matrix layer. In this research, microstructural study of layers of the stearic acid by using Scanning Electron Microscope (SEM) was carried out to find out the surface morphology of stearic acid. X-Ray Difraction (XRD) measurements were conducted to identify the crystal structure of stearic acid while Fourier Transform Infrared (FTIR) measurements were used to determine the stearic acid functional group. The Scanning Electron Microscope (SEM) results show the surface of the cavity and pore layers of the polystyrene layer was coated with white fibers homogeneously deposited on the surface of QCM / Polystyrene. Furthermore, the X-Ray Difraction (XRD) results showing a spectrum peak at an angle of 2q = 26,66° indicates the existence of stearic acid crystals. Whereas, the measurement results of the Fourier Transform Infrared (FTIR) indicate the appearance of C-H functional groups at a wavelength value of 3600-2600 cm-1 which indicates the functionality of the stearic acid layer.